Optimization of Human Resources (HR) to Support Blue Economy in Riau Island Province - Afrian Ginanjar; Ade Adriyadi (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
Riau Island Province (Kepri) has great potential to support blue economy policies with its territory dominated by oceans (96%) and strategic position on the ASEAN border. Blue economy is an important approach to integrating maritime sectors such as fisheries, marine tourism, renewable energy, and marine technology sustainably. This article aims to analyze the challenges and opportunities in optimizing local human resources (HR) to support the implementation of blue economy policies in Kepri, in order to realize the vision of